2019
DOI: 10.1097/ju.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Anterior Urethral Strictures: Toward a Better Understanding of Stricture Pathophysiology

Abstract: Introduction: Histopathology can provide insights into disease mechanism, but to date has been poorly described in urethral strictures. The purpose of this study was to comprehensively describe the histopathologic findings from stricture specimens obtained at the time of anterior urethroplasty (AU). Methods: All pathologic specimens from men undergoing AU for USD from 2010-2017 at a single institution were re-reviewed by a single, blinded pathologist who was directed to rule out lichen sclerosus (LS) and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…While an infectious etiology of LS has been actively studied, there is no consensus that bacterial infection is a cause [10]. While some groups have implicated Borrelia burgdorferi [25], evidence is ultimately poor with an unknown direction of association.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While an infectious etiology of LS has been actively studied, there is no consensus that bacterial infection is a cause [10]. While some groups have implicated Borrelia burgdorferi [25], evidence is ultimately poor with an unknown direction of association.…”
Section: Resultsmentioning
confidence: 99%
“…One poorly understood inflammatory condition that negatively impacts the male urethra is genitourinary lichen sclerosus (LS) [10]. LS is a chronic, inflammatory condition of unknown etiology that can result in urethral stricture disease (USD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis that lichen sclerosus could be a cause of GCs in bulbar urethral strictures was challenged by a study that found that lichen is almost always situated in the penile urethra rather than in the bulbar region [25] , [26] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Causes of strictures include poor vascularization resulting in contracture of buccal or skin grafts used or increased local inflammation. [ 20 ] Mechanisms to modulate the inflammatory process during urethral healing would help reduce the risk of this postoperative complication and decrease patient morbidity. This may be achieved with intraoperative application of anti‐inflammatory nanofibers to the urethroplasty to enhance the postoperative healing process.…”
Section: Discussionmentioning
confidence: 99%